2014
DOI: 10.1016/j.actbio.2014.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Optimized polymeric film-based nitric oxide delivery inhibits bacterial growth in a mouse burn wound model

Abstract: Nitric oxide (NO) has many biological roles (e.g., antimicrobial agent, promoter of angiogenesis, prevention of platelet activation, etc.) that make NO releasing materials desirable for a variety of biomedical applications. Localized NO release can be achieved from biomedical grade polymers doped with diazeniumdiolated dibutylhexanediamine (DBHD/N2O2) and poly(lactic-co-glycolic acid) (PLGA). In this study, the optimization of this chemistry to create film/patches that can be used to decrease microbial infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 57 publications
2
65
1
Order By: Relevance
“…The NO-releasing layer consisted of E2As with 25 weight% DBHD/NONO and 5, 10, or 25 weight% PLGA additives. Twenty-five weight% DBHD/NONO has been found to be optimum in terms of providing sufficient NO for extended release lifetimes [39, 40, 44]. The E2As top coat is used to prevent/reduce leaching of DBHD/NONO, neutralize the surface charge, and yield a smoother finish to the surface [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NO-releasing layer consisted of E2As with 25 weight% DBHD/NONO and 5, 10, or 25 weight% PLGA additives. Twenty-five weight% DBHD/NONO has been found to be optimum in terms of providing sufficient NO for extended release lifetimes [39, 40, 44]. The E2As top coat is used to prevent/reduce leaching of DBHD/NONO, neutralize the surface charge, and yield a smoother finish to the surface [40].…”
Section: Resultsmentioning
confidence: 99%
“…B.) [40, 41, 44]. The specific properties (i.e., acid or ester end groups) of the PLGA additives were previously studied in terms of their initial NO burst release effects, where PLGAs with acid end groups were found to produce an unwanted burst release from DBHD/NONO [40, 41].…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide releasing polymers have also provided a potential strategy for use as active wound healing dressings, capable of reducing bacterial infections at wound sites and accelerating the wound healing process for incisional and excisional wounds, 179,219,221 burn wounds, 290 and diabetic wounds. 232 While normal fibroblasts do not synthesize NO, it has been demonstrated that fibroblasts isolated from the regular wound can release NO.…”
Section: Applications Of No Releasing/generating Polymers For Preparimentioning
confidence: 99%
“…120,221 Brisbois et al tested the antibacterial efficacy of DBHD/N 2 O 2 and PLGA (5050DLG1A) doped biomedical grade PU films as a dressing for burn wounds (10 cm 2 and partial thickness) in a mouse model. 290 Burn wounds are quite common, but difficult to treat and often lead to infections. 111 The burn wounds in mice were inoculated by A. baumannii for 24 h prior to application of the NO and control wound dressings.…”
Section: Applications Of No Releasing/generating Polymers For Preparimentioning
confidence: 99%
“…3537 While silver has been found to be an effective antimicrobial agent, it has also demonstrated concerns for cytotoxicity. 38, 39 Antimicrobial peptides are also being studied in great detail but due to the complexity of their interactions, 40 they are not a popular class of practically useful antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%